1988
DOI: 10.1051/jphys:01988004902028900
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the elastic behaviour of silica aerogels taken as a percolating system

Abstract: 2014 Des mesures de module d'Young par la méthode de flexion trois points pour des aérogels de silice sont présentées. Le comportement élastique est étudié en fonction de la densité apparente des matériaux. L'analyse de ces résultats expérimentaux est effectuée en utilisant l'analogie avec un système de percolation. Abstract. 2014 Measurements of the Young modulus of silica aerogels are performed using the three points flexural technique. The elastic behaviour is studied as a function of the apparent density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
16
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 20 publications
(31 reference statements)
9
16
0
1
Order By: Relevance
“…The plastic strain which leads to a bulk density increase is associated with a decrease of the elastic modulus. This evolution of the elastic constant of the aerogel as a function of p is completely different from that already published in the literature [4][5][6][7][8][9], as discussed in the introduction.…”
Section: Av Vomentioning
confidence: 75%
See 3 more Smart Citations
“…The plastic strain which leads to a bulk density increase is associated with a decrease of the elastic modulus. This evolution of the elastic constant of the aerogel as a function of p is completely different from that already published in the literature [4][5][6][7][8][9], as discussed in the introduction.…”
Section: Av Vomentioning
confidence: 75%
“…In the case of aerogels several studies have shown that the evolution of the elastic moduli is a power law of the bulk density with an exponent in the range 2.9-3.8. This power law evolution has been observed whatever the kind of catalyst used [4--6] but also in the case of sintered aerogels [4]. The exponent value has been discussed in terms of percolation theory [4,7] and also fractal structures [8,9].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although values vary depending on aerogel preparation, untreated silica aerogels with densities near 0.1 g/mL exhibit Young's moduli near 1.0 MPa. Studies by other groups have investigated the nature of the exponent in the power law (Woignier et al [6], Scherer et al [2], and Pirard and Pirard [10]). Significant work has also been done to strengthen aerogels using a variety of methods including aging (Einarsrud et al [11]) the addition of fibers (Parmenter and Milstein [12]) and cross-linking (Leventis et al [13], Meador et al [14], and Boday et al [15]).…”
Section: Introductionmentioning
confidence: 97%